2009
DOI: 10.1111/j.1365-2141.2009.07923.x
|View full text |Cite
|
Sign up to set email alerts
|

A population pharmacokinetic model for pegylated‐asparaginase in children

Abstract: Summary We analysed 1221 serum activity measurements in 168 children from the Berlin‐Frankfürt‐Münster acute lymphoblastic leukaemia studies, ALL‐BFM (Berlin‐Frankfürt‐Münster) 95 and ALL‐BFM REZ, in order to develop a pharmacokinetic model describing the activity‐time course of pegylated (PEG)‐asparaginase for all dose levels. Patients received 500, 750, 1000 or 2500 U/m2 PEG‐asparaginase on up to nine occasions. Serum samples were analysed for asparaginase activity and data analysis was done using nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The well-known PK profile (increased elimination with time) of pegaspargase was confirmed in this study (Panetta et al, 2009;Hempel et al, 2010;Borghorst et al, 2014) (Fig. 4).…”
Section: Discussionsupporting
confidence: 79%
“…The well-known PK profile (increased elimination with time) of pegaspargase was confirmed in this study (Panetta et al, 2009;Hempel et al, 2010;Borghorst et al, 2014) (Fig. 4).…”
Section: Discussionsupporting
confidence: 79%
“…The GOF plot for the population predictions versus the observed ASNase activity levels (Figure 4) as well as the individual predictions versus [8,9]. To our knowledge, the presented model is the first reported PopPK model for ASNase medac TM .…”
Section: Assessment Of Bioequivalence Between a Recombinant Asnase Anmentioning
confidence: 90%
“…On the contrary, the PE-Gylated preparation is best described by a nonlinear elimination. Population pharmacokinetic (PopPK) analyses proposed a 1-compartment model with either timedependent clearance or Michaelis-Menten elimination [8,9]. A PopPK model for the native E. coli ASNase preparation is still lacking.…”
mentioning
confidence: 99%
“…But the phenomenon of increased drug clearance has been observed in a subgroup of pediatric patients treated for ALL without any clinical evidence of an allergic reaction. 54,55) Armstrong et al 56) showed that the presence of anti-PEG was very closely associated with rapid clearance of PEG-ASNase.…”
Section: The Likely Impact Of Immunological Responsementioning
confidence: 99%